Pancreatic metabolism, blood flow, and β-cell function in obese humans. - Honka H; Hannukainen JC; Tarkia M; Karlsson H; Saunavaara V; Salminen P; Soinio M; Mikkola K; Kudomi N; Oikonen V; Haaparanta-Solin M; Roivainen A; et al. (My University, 2022)
Context:
Glucolipotoxicity is believed to induce pancreatic β-cell dysfunction in obesity. Previously, it has not been possible to study pancreatic metabolism and blood flow in humans.
Objective:
The objective of the study was to investigate whether pancreatic metabolism and blood flow are altered in obesity using positron emission tomography (PET). In the preclinical part, the method was validated in animals.
Design:
This was a cross-sectional study.
Setting:
The study was conducted in a clinical research center.
Participants:
Human studies consisted of 52 morbidly obese and 25 healthy age-matched control subjects. Validation experiments were done with rodents and pigs.
Interventions:
PET and magnetic resonance imaging studies using a glucose analog ([18F]fluoro-2-deoxy-d-glucose), a palmitate analog [14(R,S)-[18F]fluoro-6-thia-heptadecanoic acid], and radiowater ([15O]H2O) were performed. In animals, a comparison between ex vivo and in vivo data was performed.
Main Outcome Measures:
Pancreatic glucose/fatty acid (FA) uptake, fat accumulation, and blood flow parameters of β-cell function were measured.
Results:
PET proved to be a feasible method to measure pancreatic metabolism. Compared with healthy participants, obese participants had elevated pancreatic FA uptake (P < .0001), more fat accumulation (P = .0001), lowered glucose uptake both during fasting and euglycemic hyperinsulinemia, and blunted blood flow (P < .01) in the pancreas. Blood flow, FA uptake, and fat accumulation were negatively associated with multiple markers of β-cell function.
Conclusions:
Obesity leads to changes in pancreatic energy metabolism with a substrate shift from glucose to FAs. In morbidly obese humans, impaired pancreatic blood flow may contribute to β-cell dysfunction and in the pathogenesis of type 2 diabetes.